2021
DOI: 10.2147/idr.s289907
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Second-Line Anti-TB Drugs in Cambodia: A Phenotypic and Genetic Study

Abstract: Background: Due to the emergence of Mycobacterium tuberculosis (M.tb) clinical isolates resistant to most potent first-line drugs (FLD), second-line drugs (SLD) are being prescribed more frequently. We explore the genetic characteristics and molecular mechanisms of M.tb isolates phenotypically resistant to SLD, including pre-extensively drug-resistant (pre-XDR) and extensively drug-resistant (XDR) isolates. Methods: Drug-resistant (DR) M.tb isolates collected from 2012 to 2017 were tested using sequencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
3
2
0
Order By: Relevance
“…Consistent with studies done elsewhere, among patients resistant to FQ in our study, resistance was mostly conferred by the gyrA [ 16 , 28 , 29 ] locus whereas resistance to second-line IA was mainly conferred by the rrs gene at codon A1401G [ 30 ]. Additionally, five eis C14T mutations were detected in the eis gene locus and led to low-level resistance to KAN [ 31 ], of which four occurred independent of mutations in the rrs gene.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with studies done elsewhere, among patients resistant to FQ in our study, resistance was mostly conferred by the gyrA [ 16 , 28 , 29 ] locus whereas resistance to second-line IA was mainly conferred by the rrs gene at codon A1401G [ 30 ]. Additionally, five eis C14T mutations were detected in the eis gene locus and led to low-level resistance to KAN [ 31 ], of which four occurred independent of mutations in the rrs gene.…”
Section: Discussionsupporting
confidence: 91%
“…According to our analysis, the most common rrs gene mutation was in A1401G (45.5%). Similar studies have reported high frequencies of mutation in codon A1401G ( Cheng et al., 2021 ; Jian et al., 2018 ; Rufai et al., 2020 ). The gyrB and eis genes were found to be mutation free in the MDR strains in our study.…”
Section: Discussionsupporting
confidence: 75%
“…The most frequently observed mutations were in codons A90V, D94N / D94Y , and S91P (77.3%, 4.5%, and 4.5%, respectively). According to several studies, the majority of mutations linked with FQ resistance occurred in codons A90V and D94N / D94Y in the gyrA gene ( Brossier et al., 2016 ; Chen et al., 2012 ; Cheng et al., 2021 ; Jian et al., 2018 ). According to our analysis, the most common rrs gene mutation was in A1401G (45.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Our report showed that katG gene mutation was found at the rate of 79.7%, in which 95.7% had mutations in katG315 codon and 4.3% harbored mutation in katG365 codon. The percentage of 79.7% for the katG gene mutation was consistent with earlier studies in Thailand (Boonaiam et al 2010) (Suthum et al 2020) and other Southeast Asian Countries (Ismail et al 2016) (Caws et al 2006) (Valvatne et al 2009) (Liu et al 2018) (Cheng et al 2021). The prevalence of katG315 mutation varied according to the geographical region: Southeast Asia (78.4%) (Seifert et al 2015), Vietnam (85.3%) (Hang et al 2019), China (59.4%) (Wu et al 2006), the Netherlands (53%) (Van Soolingen et al 2000), Japan (22%) (Ando et al 2010) and Singapore (26%) (Lee et al 1999).…”
Section: Discussionsupporting
confidence: 89%